2003
DOI: 10.1007/s00122-003-1330-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selection methods for optimizing genetic gain and gene diversity in a red pine (Pinus resinosa Ait.) seedling seed orchard

Abstract: Four selection methods, individual selection (IS), family selection (FS), family plus within-family selection (FWFS) and combined selection (CS), were used to estimate genetic gain [ E( g)] for stem volume and gene diversity ( GD) for ten theoretical selection intensities in a 108-family, 12-year-old red pine seedling seed orchard. Estimated genetic gain for stem volume ranged from 4.6% to 11.8% across all selection methods and intensities with CS consistently having the highest gains and FS the lowest for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…To effectively utilize the breeding seed orchard as a seed orchard, strong selection intensity must be applied in order to produce seeds with high genetic gain, whereas the orchard size, the numbers of replication and their randomization patterns determine the quality of the progeny test and the genetic information required for improving selection precision (Barnes 1995;David et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To effectively utilize the breeding seed orchard as a seed orchard, strong selection intensity must be applied in order to produce seeds with high genetic gain, whereas the orchard size, the numbers of replication and their randomization patterns determine the quality of the progeny test and the genetic information required for improving selection precision (Barnes 1995;David et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of group coancestry means inbreeding in the next generation if successful gametes unite at random (Cockerham 1967;Lindgren & Mullin 1998). The group coancestry (Θ) of the breeding seed orchard, which describes the probability that two genes are identical by descent, was calculated based on the family representation David et al 2003).…”
Section: Predicting Genetic Diversity Estimated By Status Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Breeding seedling orchards (Barnes, 1995) represent a unique situation where both breeding and production populations are included in one location where progeny test evaluation and parental selections for seed production are done in a concurrent fashion. This model is ideal for the situation where resources are limited and/or the justification for a full traditional breeding-testing-selection cycle and seed production is difficult (Barnes, 1995;David et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors, the genetic gain depends on selection intensity and heritability (a phenotypic variance ratio attributable to the genetic load of the individual) (Borrel, 2002). In addition, studies have shown the need to have a wide genetic basis (genetic diversity) for the long-term maintenance of the genetic gain in quantitative traits (Zheng, 1997;David et al, 2003;Kang et al, 2005). (Mora et al, 2007).…”
Section: Introductionmentioning
confidence: 99%